Changing Trends in Drug Overdose Mortality in Kentucky: An Examination of Race and Ethnicity, Age, and Contributing Drugs, 2016-2020. (January 2023) - Slavova, Svetla; Freeman, Patricia R.; Rock, Peter; Brancato, Candace; Hargrove, Sarah; Liford, Madison; Quesinberry, Dana; Walsh, Sharon L.
Objectives: Increased drug overdose mortality among non-Hispanic Black people in the United States in the past 5 years highlights the need for better tailored programs and services. We evaluated (1) changes in drug overdose mortality for various racial and ethnic groups and (2) drug involvement to inform drug overdose prevention efforts in Kentucky. Methods: We used Kentucky death certificates and postmortem toxicology reports from 2016-2020 (provisional data) to estimate changes in age-adjusted drug overdose death rates per 100 000 standard population. Results: The age-adjusted drug overdose death rate per 100 000 standard population among non-Hispanic Black residents doubled from 2016 (21.2) to 2020 (46.0), reaching the rate among non-Hispanic White residents in 2020 (48.7; P = .48). From 2016 to 2020, about 80% of these drug overdose deaths involved opioids; heroin involvement declined about 20 percentage points; fentanyl involvement increased about 30 percentage points. The number of psychostimulant-involved drug overdose deaths increased 513% among non-Hispanic Black residents and 191% among non-Hispanic White residents. Cocaine-involved drug overdose deaths increased among non-Hispanic Black residents but declined among non-Hispanic White residents. Drug overdose death rates were significantly lower among Hispanic residents than among non-Hispanic White residents. Conclusions: Increased opioid-involved overdose deaths among non-Hispanic Black residents in Kentucky in combination with rapidly expanding concomitant psychostimulant involvement require increased understanding of the social, cultural, and illicit market circumstances driving these rapid trend changes. Our findings underscore the urgent need to expand treatment and harm reduction services to non-Hispanic Black residents with substance use disorder.